UJI PRODUK MODEL BACA-TULIS AKUISISI LITERASI PADA PAUD - KB - TK DI DIY - Tadkiroatun Musfiroh (Jurnal Kependidikan, 2009)
This study was aimed at testing the Literacy-Acquisition Reading-Writing model against the Traditional model, the Cantol Raudhoh model (CR), the Phonic model, and and the Rapid Reading model in the learning of reading for children of 3-6 years of age. The study was carried out using an experimental design (pretest-posttest control group design). Subjects were grouped into age-groups of 3-4 years, 4-5 years, and 5-6 years. The results of the study showed that (a) compared to the Traditional model, BTAL was better in all components of reading and writing for all levels of ages, except for the BTR component for children of 5-6 years; (b) compared to the Cantol Raudhoh (CR) model, BTAL was better in the components of BTP, reading interest, writing interest, symbol sensitivity, and writing foundation, but not of BTR and reading foundation; (c) compared to the Phonic model, BTAL was better in almost all components of reading and writing for all levels of ages except for the BTR component for children of 3-4 years; and (d) compared to the CCBM model, BTAL was better in all components for all levels of ages.Key words: literacy-acquisition reading-writing model, BTAL, traditional model, cantol roudhoh model, phonic model, and CCBM, reading interest, writing interest, symbol sensitivity